Pengaruh Pembelajaran Berbasis Projek Terhadap Kemampuan Menulis Puisi Siswa Di SMKN 1 Janapria: The Effect of Project-Based Learning on Students' Poetry Writing Skills at SMKN 1 Janapria - Indrawan, Ahmad Sujardi (Literasi: Jurnal Pendidikan Guru Indonesia, 2025)
This study aims to examine the effect of project-based learning on students’ poetry writing skills at SMKN 1 Janapria. The research employed an experimental method with a pretest-posttest design, in which students were assigned poetry writing tasks before and after the implementation of the project-based learning model. The results indicate a significant improvement in students’ poetry writing abilities following the application of this approach. Enhancements were observed in aspects such as creativity, diction selection, use of figurative language, and active student engagement throughout the learning process. These findings suggest that project-based learning is effective in enhancing students’ poetry writing skills and can be recommended as an alternative method in Indonesian language instruction at vocational high schools, particularly for developing students’ creative literacy skills.